The Fate of the Jews of the Mazeikiai District during the Second World War - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2006)
In the summer of 1941, when Germany declared war on the USSR and the Red Army withdrew from Lithuania, units of insurgents formed all over the Mažeikiai district. Some joined because of their idealistic motives, hoping that Lithuania would be free again; others expected to be well paid for their services; others out of fear of being arrested for their sympathies with the Soviets in 1940 and 1941; or, on the contrary, they were disappointed in the policies of the new Soviet order, and had suffered from it (had had their land taken away, had their families exiled, etc). The men patrolled towns, protected the residents from marauders, and arrested retreating Red Army troops and former Soviet activists.The mass arrests of Jews in Ylakiai and Mažeikiai are thought to have started in early July, and in other places in approximately mid-July.Usually whole Jewish families were arrested and held in synagogues (they could be found in the centres of all small rural districts), and sometimes in barns, cellars and elsewhere. Their property was registered, and the empty houses boarded up. The items on lists were taken to warehouses and stored until their execution. Jews were held in captivity for about two weeks (the Jews in Mažeikiai perhaps longer). Men were kept separately from the women, children and old people. While they were held, they had to work: to sweep the streets, weed crops, store wood, and so on. Sometimes they were subjected to degrading treatment. Mostly local people supplied them with food.The Jews from Mažeikiai were shot in the Jewish cemetery not far from the River Venta at the end of July; those who had been brought from other places were killed in early August. The killings lasted for three or four days, with members of the auxiliary police called baltaraiščiai (they wore white armbands) from Mažeikiai and the rural districts and policemen taking part. There is no doubt that German officers took part only on the first day.The number killed there is different in different documents: from 3,000 according to eyewitnesses to 4,000 according to the commission which exhumed their remains in 1944. The study shows that both numbers, especially the second, are greatly exaggerated. The number of victims was about 2,500.Jews from Ylakiai were the only ones who were not taken to Mažeikiai. Their number did not exceed 400, and all of them were shot and buried in the town's Jewish cemetery.Their property was divided among the baltaraiščiai; less valuable things were sold to local residents.
Keywords: German occupation; Mažeikiai; Jews; Holocaust; Second World War